Modeling the effects of drug binding on the dynamic instability of microtubules - Hinow, Peter; Rezania, Vahid; Lopus, Manu; Jordan, Mary Ann; Tuszynski, Jack A. (My University, 2011)
We propose a stochastic model that accounts for the growth, catastrophe and rescue processes of steady state microtubules assembled from MAP-free tubulin in the possible presence of a microtubule associated drug. As an example for the latter, we both experimentally and theoretically study the perturbation of microtubule dynamic instability by S-methyl-D-DM1, a synthetic derivative of the microtubule-targeted agent maytansine and a potential anticancer agent. Our model predicts that among drugs that act locally at the microtubule tip, primary inhibition of the loss of GDP tubulin results in stronger damping of microtubule dynamics than inhibition of GTP tubulin addition. On the other hand, drugs whose action occurs in the interior of the microtubule need to be present in much higher concentrations to have visible effects.
Keywords: microtubules; dynamic instability; stochastic modeling